Review: Peningkatan Produktifitas Solar Still Menggunakan Kondensor - Muhammad Irfan; Dan Mugisidi (Prosiding Seminar Nasional Teknoka, 2025)
The condenser is a key component in solar desalination systems that converts water vapor into fresh water through the condensation process. The efficiency of the condenser greatly affects the amount of fresh water produced. This study aims to review the development of research on the application of salt pond condensers in seawater desalination processes. The method used is a literature review of various scientific journals that discuss internal, external, spiral and conical condenser designs and their integration with solar still systems. The results of the study show that external condensers can increase productivity, while conical condensers increase efficiency. In addition, salt ponds have the potential to become a natural condensation medium that can store heat and improve system performance. This concept can be the basis for the development of efficient, economical, and environmentally friendly desalination technology to meet the need for clean water in coastal areas of Indonesia.